Epitaxial Growth of Phosphorene on Cu Substrate: The Essential Role of Interface Strain - Niu, Tianchao; Gao, Wenjin; Xu, Ke; Wang, Xue‐Sen; Zhou, Miao (Advanced functional materials, 2025)
Two‐dimensional (2D) material epitaxially grown on a metal substrate with precise lattice registry and strong bonding can result in substantial strain within both the 2D layer and the metal surface. In turn, the strain energy has a pronounced influence on the morphology and physical properties of epitaxial films. Here, through a comprehensive approach by combining scanning tunneling microscopy and atomistic simulations, it is demonstrated that monolayer ultraflat blue phosphorene (blueP) and the topmost Cu(111) layer are in the perfect atomic registry. This Cu layer undergoes significant compressive strain, giving rise to a semi‐coherent interface between the blueP‐attached Cu layer and the underlying Cu layers. Straight and spiral dislocation patterns are observed due to strain relief, which strongly depends on the thermal annealing temperature. Dislocation lines intersect to form periodic nodes that can adopt multiple atomic arrangements correlated to the dislocation patterns. Stone‐Wales defects are distinctly imaged within the blueP layer, exhibiting periodic corrugations along the dislocation lines due to the presence of interface strain. This work underscores the potential of epitaxial layers with strong interfacial interactions as promising model systems for exploring dislocation theory and the implication for material functionality engineered by strain. Monolayer ultraflat blue phosphorene binds strongly with the topmost Cu(111) layer in a perfect atomic registry, giving rise to a semi‐coherent interface with compressive strain. Linear and spiral dislocation patterns are observed. Dislocation lines intersect to form periodic nodes that adopt multiple atomic arrangements correlated to the dislocation patterns.